2016
DOI: 10.1002/dev.21413
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated With the development of motor proficiency in school children of Kolkata: A cross‐sectional study to assess the role of chronic nutritional and socio‐economic status

Abstract: Chronic undernutrition and lower SES are associated with poorer motor proficiency in children. Understanding the complex interrelationships that shape childen's motor skills can help inform the development of health promotion programs and tailored interventions to help children reach their full potential. © 2016 Wiley Periodicals, Inc. Dev Psychobiol 58:734-744, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
0
10
0
7
Order By: Relevance
“…It is often argued that the age span between 6 and 12 years are critical for motor skill learning, however well-designed studies are scarce and more recent studies do not provide clear evidence that learning curves differ dramatically between age groups [ 32 ]. However, besides biological factors also socio-economic environment might have had different influences on groups as it has been shown that motor performance is influenced by home environment, nutritional supply and socio-economic factors [ 33 ]. To the best of our knowledge, we tried to avoid this possible bias, as schools of the CG were chosen by comparable surroundings to OGs schools such as infrastructure and neighbourhood of the school.…”
Section: Discussionmentioning
confidence: 99%
“…It is often argued that the age span between 6 and 12 years are critical for motor skill learning, however well-designed studies are scarce and more recent studies do not provide clear evidence that learning curves differ dramatically between age groups [ 32 ]. However, besides biological factors also socio-economic environment might have had different influences on groups as it has been shown that motor performance is influenced by home environment, nutritional supply and socio-economic factors [ 33 ]. To the best of our knowledge, we tried to avoid this possible bias, as schools of the CG were chosen by comparable surroundings to OGs schools such as infrastructure and neighbourhood of the school.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Morley, Till, Ogilvie, and Turner () have used the BOT‐2 assessment and found that young children (Ages 4–7) with high SES significantly outperformed middle and/or low SES for total, fine, and gross motor proficiency. Another study using the BOT‐2 has also associated lower SES with poorer motor proficiency in children aged between 5 and 12 years (Ghosh, Ghosh, Chowdhury, Wrotniak, & Chandra, ).…”
Section: Introductionmentioning
confidence: 98%
“…Previous research has also shown that gross motor competence is associated with socioeconomic status (SES) [23][24][25]. Children living in disadvantaged circumstances have fewer chances of participating in organized physical activity and sports [9], which hampers the development of such specific skills.…”
Section: Introductionmentioning
confidence: 99%